Evaluation of gene, protein and neurotrophin expression in the brain of mice exposed to space environment for 91 days. - Daniela Santucci; Fuminori Kawano; Takashi Ohira; Masahiro Terada; Naoya Nakai; Nadia Francia; Enrico Alleva; Luigi Aloe; Toshimasa Ochiai; Ranieri Cancedda; Katsumasa Goto; Yoshinobu Ohira (PLoS ONE, 2012)
Effects of 3-month exposure to microgravity environment on the expression of genes and proteins in mouse brain were studied. Moreover, responses of neurobiological parameters, nerve growth factor (NGF) and brain derived neurotrophic factor (BDNF), were also evaluated in the cerebellum, hippocampus, cortex, and adrenal glands. Spaceflight-related changes in gene and protein expression were observed. Biological processes of the up-regulated genes were related to the immune response, metabolic process, and/or inflammatory response. Changes of cellular components involving in microsome and vesicular fraction were also noted. Molecular function categories were related to various enzyme activities. The biological processes in the down-regulated genes were related to various metabolic and catabolic processes. Cellular components were related to cytoplasm and mitochondrion. The down-regulated molecular functions were related to catalytic and oxidoreductase activities. Up-regulation of 28 proteins was seen following spaceflight vs. those in ground control. These proteins were related to mitochondrial metabolism, synthesis and hydrolysis of ATP, calcium/calmodulin metabolism, nervous system, and transport of proteins and/or amino acids. Down-regulated proteins were related to mitochondrial metabolism. Expression of NGF in hippocampus, cortex, and adrenal gland of wild type animal tended to decrease following spaceflight. As for pleiotrophin transgenic mice, spaceflight-related reduction of NGF occurred only in adrenal gland. Consistent trends between various portions of brain and adrenal gland were not observed in the responses of BDNF to spaceflight. Although exposure to real microgravity influenced the expression of a number of genes and proteins in the brain that have been shown to be involved in a wide spectrum of biological function, it is still unclear how the functional properties of brain were influenced by 3-month exposure to microgravity.